Development of a rectal sexually transmitted infection (STI) Model in Rhesus macaques using Chlamydia trachomatis serovars E and L2. Issue 5 (10th May 2017) - Henning, Tara R.; Morris, Monica; Ellis, Shanon; Kelley, Kristen; Phillips, Christi; Ritter, Jana; Jones, Tara; Nachamkin, Eli; Chen, Cheng Y.; Hong, Jaeyoung; Kang, Joseph; Patton, Dorothy; et al.
Abstract: Background: Rectal STI coinfection models enhance the understanding of rectal HIV transmission risk factors. Materials and Methods: Rhesus macaques (n=9) were exposed to one of three rectal Chlamydia trachomatis (CT) challenges: C . trachomatis L2 (CT‐L2 ); C . trachomatis serovar E (CT‐E), followed by CT‐L2 ; or CT‐E, treatment/clearance, then CT‐L2 . Infections were monitored by PCR. Weekly blood and rectal secretion/lavage samples were collected for cytokine analyzes and/or epithelial sloughing, occult, and overt blood determinations. Results: Chlamydial infections were successfully established in each animal, with varying degrees of persistence. Mucosal IL‐1beta was upregulated in animals consecutively infected with CT‐E then CT‐L2 ( P =.05). Epithelial sloughing was also significantly increased post‐infection in this group ( P =.0003). Conclusions: This study demonstrates successful rectal infection of rhesus macaques with CT‐E and CT‐L2 and describes measures of assessing rectal inflammation and pathology. Different infection strategies yield varying inflammatory and pathologic outcomes, providing well‐described models for future SIV/SHIV susceptibility studies.